Rockton : Watcher in the Woods - Book 4 - Armstrong, Kelley (New York : Minotaur Books, 2019)
"When a US Marshal shows up demanding the release of one of the residents, but won't say who, Casey and her boyfriend, Sheriff Eric Dalton, are skeptical. And yet only hours later, the marshal is shot dead and the only possible suspects are the townspeople and Casey's estranged sister, smuggled into town to help with a medical emergency. It's up to Casey to figure out who murdered the marshal, and why someone would kill to keep him quiet."--Provided by publisher.
Keywords: Duncan, Casey -- (Fictitious character) -- Fiction; United States marshals -- Fiction; Criminals -- Fiction; Victims of crimes -- Fiction. -- Protection; Secrecy -- Fiction; Murder -- Fiction. -- Investigation; Yukon -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Novels